2017
DOI: 10.1021/acsami.7b14957
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of MoS2 Nanosheets and VS2 for the Hydrogen Evolution Reaction with Enhanced Humidity-Sensing Performance

Abstract: As a typical transition-metal dichalcogenides, MoS has been a hotspot of research in many fields. In this work, the MoS nanosheets were compounded on 1T-VS nanoflowers (VS@MoS) successfully by a two-step hydrothermal method for the first time, and their hydrogen evolution properties were studied mainly. The higher charge-transfer efficiency benefiting from the metallicity of VS and the greater activity due to more exposed active edge sites of MoS improve the hydrogen evolution reaction performance of the nanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 41 publications
3
95
0
Order By: Relevance
“…22 Theoretical studies have also shown the metallic VS 2 to display an excellent HER performance compared with other TMDCs. 29,30 From the above mentioned factors, we present a facile one-step cost-effective hydrothermal method to produce VS 2 nanodiscs (NDs), without the need of catalysts, substrates, or templates at low temperature. 25 Given the high conductivity with stable structure favoring rapid electron transport, VS 2 -based nanostructures could be a highly promising material for HER activity.…”
Section: Introductionmentioning
confidence: 99%
“…22 Theoretical studies have also shown the metallic VS 2 to display an excellent HER performance compared with other TMDCs. 29,30 From the above mentioned factors, we present a facile one-step cost-effective hydrothermal method to produce VS 2 nanodiscs (NDs), without the need of catalysts, substrates, or templates at low temperature. 25 Given the high conductivity with stable structure favoring rapid electron transport, VS 2 -based nanostructures could be a highly promising material for HER activity.…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium disulfide (VS 2 ) has been widely studied as an emerging electrocatalyst material for hydrogen‐evolution reactions, because of its catalytic activity both on the basal plane and at the edges . Because of its good conductivity and abundant active sites, layered VS 2 also holds great potential in the hydrogen‐evolution reaction . Very few composite materials of VS 2 (e.g., with MoS 2 and C 3 N 4 ) have been developed for superior hydrogen‐evolution activity and yet, based on the calculated energy‐level alignment of VS 2 , it is a favorable candidate to form Z‐scheme heterostructures with ZnIn 2 S 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of its good conductivity and abundant active sites, layered VS 2 also holds great potential in the hydrogen‐evolution reaction . Very few composite materials of VS 2 (e.g., with MoS 2 and C 3 N 4 ) have been developed for superior hydrogen‐evolution activity and yet, based on the calculated energy‐level alignment of VS 2 , it is a favorable candidate to form Z‐scheme heterostructures with ZnIn 2 S 4 . Therefore, herein, we report the first synthesis of a noble‐metal‐free composite of ZnIn 2 S 4 –VS 2 , with the aim of forming a direct Z‐scheme composite material without an electron mediator.…”
Section: Introductionmentioning
confidence: 99%
“…The strong (002) peak of MoS 2 /VS 2 represents the good stacking of MoS 2 as the P‐VS 2 microflowers can not only prevent the agglomeration of MoS 2 nanosheets but also create numerous contact sites for the vertical growth of MoS 2 on their surface or inner pores. It is worth noting that the diffraction peak of the MoS 2 /VS 2 heterostructure at 13.8°, corresponding to the (002) plane of MoS 2 , is lower than that of pure MoS 2 (2θ = 14.4°), suggesting the enlarged interlayer distance of the (002) plane …”
Section: Resultsmentioning
confidence: 98%
“…Compared with the surfaces of VS 2 and F127‐containing VS 2 composite, distinct meso‐/macropores can be observed on the surface of P‐VS 2 microflowers (Figure S2c–f, Supporting Information and Figure a). The pure MoS 2 nanosheets (Figure b and Figure S3a–c, Supporting Information) aggregate with each other, resulting in heterogeneous micrometer‐sized spheres since the MoS 2 nanoplates would curl freely to form a closed architecture and eventually form surface petals to reduce dangling bonds and surface energy . Figure S2c,d in the Supporting Information reveals that the original nanopetal architecture of P‐VS 2 is still maintained after the thermal carbonization, which provides a stable skeleton for the self‐assembly of MoS 2 nanosheets.…”
Section: Resultsmentioning
confidence: 99%